Daun Sirih Hijau (Piper betle L) sebagai Pengganti Antibiotik pada Prostatitis - Divian Ozaza Sari; Exsa Hadibrata; Oktafany (CV. Jasa Sukses Abadi, 2019)
Prostatitis is swelling and regulation of prostate reserves, a measure of the size of walnuts placed just below the bladder in men. Prostatitis occurs in men over 50 years of age and it is estimated that about 50% of men question prostatitis during their lifetime. Treatment for prostatitis depends on the cause. Antibiotics are effective treatments for acute bacterial prostatitis. Antibiotic treatment has several factors that must be used using traditional drugs that have smaller side effects compared to materials produced from chemicals, besides that the use of natural ingredients requires a cheaper cost. Green betel leaf (Piper betle L.) is able to inhibit the growth of Escherichia coli, Streptococcus viridans, Staphylococcus aureus, Vibrio cholera and Shigella dysenteriae.